Integration of Software Defined Radio and Add-on Board into Digital Communication Education with Hands-on Applications - Emrah Genç (International Journal of Applied Methods in Electronics and Computers, 2016)
Owing to the theory depend heavily on mathematical models in communication lessons, instructors find students lost in all the equations and notations that given. Setting a lab component for students to put together the theory with practical implementations is not very easy in many times because it may cost a large number of equipment that is not low-priced. Yet there are still some solutions which reduce the cost in designing a real-life communication laboratory and effective in teaching. We present the usage of NI-USRP Software Defined Radio (SDR) and Emona DATEx Add-on Board on digital modulation techniques that take part in communication engineering education. Most commonly used digital modulation techniques; Amplitude Shift Keying (ASK), Phase Shift Keying (PSK) and Frequency Shift Keying (FSK) are analyzed in both devices. Both modulations and demodulations of mentioned techniques are done by experimentally.